PEDAGOGICAL CONTENT OF TEACHING PRIMARY CLASS STUDENTS TO LOGICAL THINKING. (International conference on multidisciplinary science, 2024)
In this article, it is discussed how to improve the logical thinking of students studying in preschool and primary school.